Safety Comparison of Laryngeal Mask Use With Endotracheal Intubation in Patients Undergoing Dacryocystorhinostomy Surgery. Issue 4 (July 2018) - Dumas, George A.; Bryant, Ayesha S.; Ibey, Justin; Long, John A.; Vicinanzo, Matthew G.; Boyd, Gwendolyn L.
Abstract : Purpose: This study will determine the safety of laryngeal mask airway (LMA) compared with endotracheal tube (ETT) in patients undergoing general anesthesia for dacryocystorhinostomy (DCR) surgery. Methods: In this retrospective cohort study, intraoperative and postoperative outcomes of patients who underwent DCR at UAB Callahan Eye Hospital using either LMA or ETT were compared. Results: Over a period of 52 months, 429 patients underwent external DCR surgery. An ETT was used in 37 patients and LMA in 392 patients. Baseline patient characteristics and anesthetic management were similar. No documented cases of blood or gastric aspiration occurred in the total cohort. Our study confirmed the findings of others that there is less cardiovascular lability on LMA placement than with ETT intubation.1 A 30% increase in heart rate from baseline after intubation (ETT 10.8%, LMA 1.8%; p = 0.010) and after incision (ETT 8.1%, LMA 1.8%; p = 0.047) occurred more frequently in the ETT group. Airway management with an LMA was also less difficult compared with an ETT (ETT 5.7%, LMA 0.5%; p = 0.035). Conclusions: The use of an LMA for airway control is safe and effective in patients undergoing general anesthesia for DCR surgery. No events of aspiration occurred with LMA use. Heart rate increase was significantly less in the LMA group. In our opinion, use of an LMA for airway control during DCR surgery is superior to use of an ETT. Airway protection, improved hemodynamics, and less difficulty in placement of the laryngeal airway device are all validated by this study. Abstract : Laryngeal mask airway use in external dacryocystorhinostomy surgery under general anesthesia is safe and offers improved hemodynamic conditions and easier placement compared to an endotracheal tube.